Dampak Stay at Home dan Social Distancing terhadap Kelangsungan Kesenian Sunda Sisingaan di Cimahi - Luki Safriana; Drajat Sulistiyono (Journal of Sustainable Business Hub, 2020)
Stay at home, social distancing and continuity of Sundanese Sundanese art in the Cimahi area. The purpose of this research is to find out and analyze stay at home, social distancing has an influence on the continuity of art in the Cimahi region. The results of the study describe the simultaneous test Y = 11,206 - 0,298 X1 + 0,091 X2. From the problems above where stay at home and social distancing are very influential, then the Cimahi city government should eliminate stay from home and social distancing when the corona virus pandemic is over, given the continuity of the arts Sunda sisingaan in the Cimahi area will be destroyed and extinct, due to not getting money to finance their activities.